Evaluating the Risk Premium in the Cross-Section of Commodity Futures - Berglund,Oliwer; Rabe Gundersen,Martin (2018)
Departing from the increased interest in and beneficial characteristics of investments in commodity futures evident in the literature. This paper evaluates the existence of factors that may explain the cross-section of commodity futures through macro, equity and commodity specific factors. The models employed are estimated through the Fama-Macbeth two step approach on individual contracts as test assets, instead of the more common approach of using portfolios as test assets. The dataset consist of 15 continuous time series of agricultural, metal and energy futures prices over a timeframe of nearly 30 years. We evaluate whether the capital inflow into commodity futures has had a significant effect on the explanatory power of our models. Further, a test for the continued segmentation between equity and commodity markets is conducted. Our findings show that the commodity futures market is segmented, as evident in the low explanatory power of the macro and equity motivated factors. We do not find any factor that can effectively price the cross-section of commodity futures in our dataset. Lastly, we identify a slight improvement of the explanatory power of some of our models relative to previous research. We credit this to the increase in capital inflow to commodity futures, as argued by previous research.
Keywords: Commodity Futures; Risk Premium; Asset Pricing Models; Fama-MacBeth; Specific Factors.